TEMPO’S PERSPECTIVE ON THE REPRESENTATION OF GOVERNMENT IN DEALING WITH COVID-19 CASES - Siti Setia Mintarsih; Denny Kodrat; Raynesa Noor Emiliasari (Universitas Islam Negeri Sunan Gunung Djati, 2020)
Tempo.co as well-known mass media in Indonesia gains tremendous attention from public reader concerning Covid-19 pandemic. The influential news that it produced has discursive dimension that can be analyzed by Critical Discourse Analysis (CDA). This study is a textual analysis that uses CDA theory with purposive sampling from tempo.co news as the data. In this study, it can be found that Tempo.co portray this media as a ‘watchdog’ that serves to supervise those who have a power within politics (government). Tempo’s newspaper produces text news that reflects to the government depiction in their policies. Thus, Tempo’s newspaper led the readers to give a positive image to Tempo.co as an active and existent media in serving the truth. Tempo.co try to gain the public trust to consume their news, then Tempo will get a high profit in it. Keywords: CDA; Ideology; Socio-culture; Mass Media